Information needs for designing a home monitoring system for children with medical complexity. (February 2019) - Nkoy, Flory L.; Hofmann, Michelle G.; Stone, Bryan L.; Poll, Justin; Clark, Lauren; Fassl, Bernhard A.; Murphy, Nancy A.
Highlights: Ca(Mo0.6W0.4)O4: Eu3+ phosphors were prepared by a low cost precipitation process. The luminescent intensity of Eu3+ increases 100% and 65% than in CaMoO4 and CaWO4. Energy transfer type among Eu3+ is exchange interaction in Ca(Mo0.6W0.4)O4 host. The refractive index of non-transparent phosphors was calculated by a new method. Abstract: Background Children with medical complexity (CMC) are a growing population of medically fragile children with unique healthcare needs, who have recurrent emergency department (ED) and hospital admissions due to frequent acute escalations of their chronic conditions. Mobile health (mHealth) tools have been suggested to support CMC home monitoring and prevent admissions. No mHealth tool has ever been developed for CMC and challenges exist. Objective To: 1) assess information needs for operationalizing CMC home monitoring, and 2) determine technology design functionalities needed for building a mHealth application for CMC. Methods Qualitative descriptive study conducted at a tertiary care children's hospital with a purposive sample of English-speaking caregivers of CMC. We conducted 3 focus group sessions, using semi-structured, open-ended questions. We assessed caregiver's perceptions of early symptoms that commonly precede acute escalations of their child conditions, and explored caregiver's preferences on the design functionalities of a novel mHealth tool to support home monitoring of CMC. We used content analysis to assess caregivers' experience concerning CMC symptoms, their responses, effects on caregivers, and functionalities of a home monitoring tool. Results Overall, 13 caregivers of CMC (ages 18 months to 19 years, mean = 9 years) participated. Caregivers identified key symptoms in their children that commonly presented 1–3 days prior to an ED visit or hospitalization, including low oxygen saturations, fevers, rapid heart rates, seizures, agitation, feeding intolerance, pain, and a general feeling of uneasiness about their child's condition. They believed a home monitoring system for tracking these symptoms would be beneficial, providing a way to identify early changes in their child's health that could prompt a timely and appropriate intervention. Caregivers also reported their own symptoms and stress related to caregiving activities, but opposed monitoring them. They suggested an mHealth tool for CMC to include the following functionalities: 1) symptom tracking, targeting commonly reported drivers (symptoms) of ED/hospital admissions; 2) user friendly (ease of data entry), using voice, radio buttons, and drop down menus; 3) a free-text field for reporting child's other symptoms and interventions attempted at home; 4) ability to directly access a health care provider (HCP) via text/email messaging, and to allow real-time sharing of child data to facilitate care, and 5) option to upload and post a photo or video of the child to allow a visual recall by the HCP. Conclusions Caregivers deemed a mHealth tool beneficial and offered a set of key functionalities to meet information needs for monitoring CMC's symptoms. Our future efforts will consist of creating a prototype of the mHealth tool and testing it for usability among CMC caregivers.